Multicultural education as policy and praxis in Finland: Heading in a problematic direction? - Gunilla Holm; Jan-Erik Mansikka (Recherches en Éducation)
In this article we discuss the state of multicultural education as both praxis and policy in Finland. Immigration is increasing year by year in this context even though it remains relatively low compared to other European countries. Multiculturalism is very much discussed in Finnish society and media at large today. Though very much present and supported in the national curriculum, many scholars argue that not enough is done to prepare teachers to deal with diversity in Finnish schools. This article confronts laws and official documents related to the issue in Finnish education (e.g., students’ experiences and praticising teachers’ views on multicultural education in the nordic country). The article concludes with a suggested urge to give more space to negotiating a common place between « Finns » and the others in education.